Avant‐Garde in the Age of Identity: Alvin Boyarsky, the Architectural Association and the Impact of Pegadogy. (2nd July 2019) - Marjanovic, Igor
Abstract: Under the stewardship of its iconic chairman Alvin Boyarsky, the Architectural Association (AA) presided over a burgeoning of architectural avant‐garde tendencies that encouraged tutors and students to expand their architectural vocabulary and outlook by embracing issues of sexuality and identity, as well as other art forms. St Louis‐based architect, historian and academicIgor Marjanovic explores this era.